Characterization and functional application of PrBa0.5Sr0.5Co1.5Fe0.5O5+δ cathode material for IT-SOFC. (May 2021) - Zan, Jianan; Wang, Shenglin; Zheng, Dingshan; Li, Fushao; Chen, Weimin; Pei, Qiming; Jiang, Long
Highlights: The double-perovskite oxide PrBa0.5 Sr0.5 Co1.5 Fe0.5 O5+ δ (PBSCF) cathode maintains the better structural stability. The mixed oxidation state of Pr 3+ /Pr 4+, Co 2+ /Co 3+, and Fe 3+ /Fe 4+ species facilitate the oxygen reduction reaction kinetics. Mössbauer Spectroscopy affirms that the proportion of Fe 3+ and Fe 4+ is 79.1 % and 20.9 %, respectively. Low polarization resistance of 0.067 Ω cm −2 and high power density of 590 mW cm −2 at 800 °C are obtained on 300μm-thickness LSGM electrolyte. Abstract: The physicochemical properties for layered perovskite PrBa0.5 Sr0.5 Co1.5 Fe0.5 O5+ δ (PBSCF) oxide are systematically investigated to gain insight into the correlation between structure, surface state and oxygen reduction reaction properties. The PBSCF sample possesses orthorhombic structure and keeps better structural stability under operating conditions. X-ray photoelectron spectra analysis indicates that the mixed oxidation state of (Co, Fe) and Pr promotes the oxygen reduction reaction kinetics by creating oxygen vacancies at the surface. Mössbauer Spectroscopy affirms that the proportion of Fe 3+ and Fe 4+ in iron species is 79.1 % and 20.9 %, respectively. The electrode polarization resistance is 0.067 Ω cm 2 at 800 °C in air. The oxygen-ion bulk diffusion plays the rate-limiting step during the electrode process. The cell with PBSCF cathode delivers the power density of 590 mW cm −2 at 800 °C. These results show the PBSCF exhibits a promising application prospect in intermediate temperature solid oxide fuel cell.